2018
DOI: 10.22159/ajpcr.2018.v11i10.25146
|View full text |Cite
|
Sign up to set email alerts
|

Euclea Crispa: Review of Its Botany, Ethnomedicinal Uses, and Pharmacological Properties

Abstract: Euclea crispa is widely used as herbal medicine in southern Africa. This study was aimed at reviewing the botany, ethnomedicinal uses, and validated pharmacological properties of E. crispa. The literature search for information on ethnomedicinal uses and pharmacological activities of E. crispa was undertaken using databases such as web of science, BMC, science direct, elsevier, scopus, PubMed, and scielo. Other relevant literature sources included books, book chapters, websites, theses, conference papers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Most medicinal uses are linked to the bulb and leaf or the entire plant in ritual or magical uses, and the species is also used mixed with other plant species (Table 1). Research by Gurib-Fakim [36] and Maroyi [37,38] revealed that traditional medicines are often prepared by combining several different plant species to effect synergistic properties or to initiate an interaction with a relevant molecular target.…”
Section: Medicinal Uses Of D Elatamentioning
confidence: 99%
“…Most medicinal uses are linked to the bulb and leaf or the entire plant in ritual or magical uses, and the species is also used mixed with other plant species (Table 1). Research by Gurib-Fakim [36] and Maroyi [37,38] revealed that traditional medicines are often prepared by combining several different plant species to effect synergistic properties or to initiate an interaction with a relevant molecular target.…”
Section: Medicinal Uses Of D Elatamentioning
confidence: 99%